Case report: Disitamab vedotin combined with immunotherapy demonstrated excellent efficacy in scrotal Paget’s disease with Her-2 overexpression - Wang, Jia-Ling; Meng, Wen-Jun; Hu, Nian; Liu, Ji-Yan (Frontiers in Immunology, 2024)
Background Extramammary Paget’s disease (EMPD) is a rare epithelial malignancy, and approximately 30%–40% of EMPD patients overexpress human epidermal growth factor receptor 2 (Her-2). Currently, there are no established standard treatments for advanced EMPD while anti–Her-2 therapy is recommended for Her-2–positive cases. Case presentation Here, we report a 51-year-old male diagnosed with advanced Her-2–positive EMPD, presenting with numerous lymph node metastases. This patient received disitamab vedotin (an antibody-drug conjugate, targeting Her-2) combined with serplulimab as first-line treatment. After seven cycles of combination therapy, the patient tolerated the treatment well and the lymph node lesions continued to shrink. However, the patient developed immunotherapy-related pneumonia following the eighth treatment. Hormone therapy was administered while all the anti-tumor therapies were halted. After the pneumonia improved, the patient underwent positron emission tomography-computed tomography, revealing a complete response to his tumor. To consolidate the effect, he received another five cycles of disitamab vedotin monotherapy as maintenance therapy, without experiencing any adverse events. To date, the patient has remained in good health without any recurrence 10 months after drug discontinuance. Conclusion Disitamab vedotin combined with immunotherapy demonstrated a long-term clinical benefit in advanced Her-2–positive EMPD. For rare solid tumors with Her-2 overexpression, disitamab vedotin combined with immunotherapy might offer a viable therapeutic choice.